Integrasi Program Tahfidz dalam Pembentukan Karakter Islami di MA Ma’arif 7 Sunan Drajat Paciran Lamongan - Wasis, Wasis (Kamil : Journal of Education, 2025)
This study aims to analyze the strategy of developing talents and interests in the tahfidz program to support the formation of students' characters at MA Ma'arif 7 Sunan Drajat Paciran Lamongan. Using a qualitative approach with a case study method, this study involved the head of the madrasah, tahfidz teachers, students, and parents as research subjects. Data were collected through interviews, observations, and documentation, which were analyzed using a thematic approach. The results of the study indicate that the main strategies applied in the tahfidz program include the talqin method, muraja'ah, and reward-based motivation. This strategy is effective in improving students' memorization while forming characters of discipline, responsibility, and honesty. The responses of teachers (88%) and students (90.74%) showed high enthusiasm for this program. However, obstacles such as limited teaching staff, minimal supporting facilities, and lack of flexibility in memorization targets are still challenges that need to be overcome